Spatial variation in population dynamics of the sand-burrowing amphipod Haustorioides japonicus - Suzuki, Yuya; Yamahira, Kazunori; Kajihara, Naoto; Takada, Yoshitake (Population ecology, 2013)
Densities of sandy beach organisms along coastlines often vary considerably even within small local scales. In order to understand the demographic basis of density variations in shore animals, we examined the population dynamics of the amphipod Haustorioides japonicus Kamihira, which is an ideal subject because it lacks a planktonic dispersal stage in its life history. Quantitative sampling at three adjacent sandy beaches along the Sea of Japan coast revealed that the spring density, i.e., the density of overwintered individuals, was similar among the three beaches. However, the amount of recruitment of newly hatched juveniles from late spring to summer greatly differed among the beaches, resulting in large spatial variations in the summer density. Cohort analyses revealed that at all beaches, young-of-the-year (YOY) individuals reproduced and then died, and that individuals which recruited in late summer overwintered. Moreover, growth, fecundity, and survival schedules of overwintered and YOY individuals were very similar among beaches. These observations suggest that the difference in recruitment success, i.e., the survival of newly hatched juveniles, is the primary cause of the inter-population variation in the summer density. It is likely that variations in salinity and sandy sediment affect the recruitment success of newly hatched individuals. This study indicates that biological productivity may differ substantially even among adjacent sandy beaches, with important implications for beach management.